Dual effects of gonadotropin-inhibitory hormone on testicular development in prepubertal Minxinan Black rabbits (Oryctolagus cuniculus) - Sang, Lei; Sun, Shikun; Wang, Jinxiang; Gao, Chengfang; Chen, Dongjin; Xie, Xiping (Frontiers in Veterinary Science, 2024)
Gonadotropin-inhibitory hormone (GnIH) is a neurohormone that not only suppresses reproduction at the brain level but also regulates steroidogenesis and gametogenesis at the gonad level. However, its function in gonadal physiology has received little attention in rabbits. The main objective of this study was to evaluate the effects of GnIH on testicular development and function in prepubertal Minxinan Black rabbits (Oryctolagus cuniculus). In the present study, we investigated the serum reproductive hormone concentration, testicular parameters, morphology of seminiferous tubules, apoptosis of testicular cells, and expression of reproductive-related genes in male prepubertal Minxinan Black rabbits intraperitoneally administered with 0, 0.5, 5, or 50 μg quail GnIH-related peptides (qGnIH) for 10 days. Compared with the vehicle, administration with 5 μg of qGnIH downregulated the serum testosterone concentration and mRNA levels of spermatogenic genes (PCNA, FSHR, INHβA, HSF1, and AR) and upregulated the apoptosis rate of testicular cells; administration with 50 μg of qGnIH decreased the serum testosterone concentration and hypothalamic GnIH gene mRNA level and increased the serum LH concentration, pituitary LHβ gene mRNA level, testicular weight, gonadosomatic index (GSI), and spermatogenic cell layer thickness. It is concluded that GnIH could exert dual actions on testicular development depending on the male prepubertal rabbits receiving different intraperitoneal doses.